2021
DOI: 10.3390/md19020092
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin@Polyvinylpyrrolidone Nanoparticles Promoted Oxidative Stress-Induced Cell Death in Caco-2 Human Colon Cancer Cells

Abstract: Fucoxanthin (FX), a natural carotenoid found in seaweed with multiple functional activities, is unstable with a poor water solubility that limits its utilization. This study aimed to improve FX’s stability and bioavailability via the nano-encapsulation of FX in polyvinylpyrrolidone (PVP)-coated FX@PVP nanoparticles (NPs). The FX@PVP NPs were evaluated in terms of their morphology, stability, encapsulation efficiency (EE), loading capacity (LC), and in vitro release to optimize the encapsulation parameters, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Cell viability levels and photoprotection were evaluated by MTT assay, a common way to evaluate the effects of various chemicals on cell growth . Briefly, RMCs were seeded in a 96-well microtiter plate at a concentration of 1 × 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability levels and photoprotection were evaluated by MTT assay, a common way to evaluate the effects of various chemicals on cell growth . Briefly, RMCs were seeded in a 96-well microtiter plate at a concentration of 1 × 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted with fucoxanthin encapsulated into casein nanoparticles, and the same but with coated chitosan, was subjected to an in vitro assay of a simulated digestion process, representing its exposure to various enzymes and secreted fluids; nevertheless, nanoparticles containing fucoxanthin successfully transform fucoxanthinol through the gastrointestinal tract [ 111 ]. A recent study showed that fucoxanthin@polyvinylpyrrolidone nanoparticles effectively delivered fucoxanthin into human colon cancer cells in vitro, confirming a new and targeted therapeutic approach [ 113 ]. However, nano-particle-based fucoxanthin treatment should be introduced in animal models before further translation into clinical trials to evaluate the extent of bioactivity.…”
Section: Safety Toxicity and Functional Stability Of Fucoxanthinmentioning
confidence: 99%
“…Interestingly, fucoxanthinol evidenced a more potent proapoptotic effect than FX in HCT116 cells via suppression of NF-κB activation [453]. Additionally, other studies using FX nanogels or nanoparticles to increase its bioavailability reported that these formulations exhibited a greater pro-oxidative activity than free FX, stimulating ROS-triggered apoptosis in Caco-2 cells [454,455]. In relation to hepatic cancer, FX in combination with cisplatin evidenced a higher antiproliferative activity than treatment with cisplatin alone in human hepatoma HepG2 cells through down-regulation of NF-κB expression as well as an increase in the Bax/Bcl-2 ratio [456].…”
Section: In Vitro Studiesmentioning
confidence: 99%